Strategic Intelligence Analysis in The Integration of National Defense Components to Counter The Threat of Nuclear Terrorism in Indonesia - Rajagukguk, M. H.; Gunawan, B.; Santoso, M.; Ratmono, B. M. (Atom Indonesia, 2025)
The development of nuclear science presents multifaceted benefits across diverse sectors, including energy, health, construction, agriculture, and food production. However, the proliferation of nuclear technology introduces the complex challenge of dual-use, encompassing both constructive applications and potential misuse for nefarious purposes such as terrorism. Indonesia, like many nations, faces this dual-use dilemma, necessitating robust defense mechanisms to safeguard against nuclear terrorism threats. This study aims to investigate and enhance Indonesia's defense system against nuclear terrorism by emphasizing integration and strategic intelligence within its defense components. The primary objective is to analyze the integration and coordination mechanisms among the main, supporting, and reserve components of Indonesia's defense system to strengthen strategic analysis and intelligence efforts in combating nuclear terrorism threats. Through a qualitative research methodology employing an analytical approach, data collection encompasses expert interviews, observations, and an extensive literature review. The study identifies various threat risks and potential initiators of nuclear terrorism attacks, highlighting the critical role of integrated defense components in addressing these threats effectively. Findings reveal the indispensable roles of the main, supporting, and reserve components in executing intelligence functions, including investigation, security, and information gathering, to mitigate the threat of nuclear terrorism. Despite their distinct roles, these components require seamless integration and coordination to maximize strategic analysis efforts and intelligence sharing. The research identifies several constraints hindering the effective implementation of integration and strategic intelligence within Indonesia's defense components. These constraints necessitate targeted improvements to enhance the nation's capability to mitigate the threat of nuclear terrorism effectively. In conclusion, this study underscores the significance of integration and strategic intelligence within Indonesia's defense system to confront the evolving threat landscape of nuclear terrorism. By addressing research gaps and proposing actionable recommendations, this research contributes to strengthening Indonesia's defense posture against nuclear terrorism, thereby ensuring national security and global stability.